A Robotic Biopsy Endoscope with Magnetic 5-DOF Locomotion and a Retractable Biopsy Punch - Hoang, Manh Cuong (Micromachines (Basel), 2020)
Capsule endoscopes (CEs) have emerged as an advanced diagnostic technology for gastrointestinal diseases in recent decades. However, with regard to robotic motions, they require active movability and multi-functionalities for extensive, untethered, and precise clinical utilization. Herein, we present a novel wireless biopsy CE employing active five degree-of-freedom locomotion and a biopsy needle punching mechanism for the histological analysis of the intestinal tract. A medical biopsy punch is attached to a screw mechanism, which can be magnetically actuated to extrude and retract the biopsy tool, for tissue extraction. The external magnetic field from an electromagnetic actuation (EMA) system is utilized to actuate the screw mechanism and harvest biopsy tissue; therefore, the proposed system consumes no onboard energy of the CE. This design enables observation of the biopsy process through the capsule’s camera. A prototype with a diameter of 12 mm and length of 30 mm was fabricated with a medical biopsy punch having a diameter of 1.5 mm. Its performance was verified through numerical analysis, as well as in-vitro and ex-vivo experiments on porcine intestine. The CE could be moved to target lesions and obtain sufficient tissue samples for histological examination. The proposed biopsy CE mechanism utilizing punch biopsy and its wireless extraction–retraction technique can advance untethered intestinal endoscopic capsule technology at clinical sites.